Virtual Mandarin Learning Tools for Interactive Online Learning. Issue 1 (February 2021) - Sofi,; Ying, Y
Abstract: Millennials like to study in groups and utilize technology in learning activities. They also like experimental learning and learning methods of "learning by doing". They can do many things at one time. This generation needs clear objectives at the beginning of their lessons and quick feedback on their curiosity. Most Mandarin literature students are from the millennial generation. For a more effective and efficient teaching and learning process, it is necessary to know the current learning styles of Mandarin Literature students. This study has three objectives as follows; First, to map the learning styles of Millennials generation who are also students of Mandarin Literature. Second, to map out the strategies needed to improve learning achievement. Third, to design tools that can improve learning achievement. The research method was carried out by distributing questionnaires to Mandarin literature students. From the results of the questionnaire, the researcher mapped the learning styles of these millennials. After that, researchers would create a learning tools that allows students to online learning independently.